2018
DOI: 10.4236/aid.2018.82009
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Effect of Home-Based Oral Chloroquine Treatment on Haematological Indices of <i>P. falciparum</i> Malaria in Children under 5 Years in Jos Metropolis

Abstract: Background: The incidence of P. falciparum malaria is characterized by high rates of morbidity and mortality in under 5 children; a trend reportedly prevalent in tropical and subtropical countries including Nigeria, and recently observed in Jos metropolis, has to date defied all constructive, preventive and drug therapy intervention measures and consequently continues to constitute a serious public health problem in this most vulnerable group. Objective: The aim of this study was to determine certain haematolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, the significant increase (p<0.05) in PCT could indicate the presence of an infection, while the significant increase (p<0.05) in HCT could suggest dehydration. These findings are consistent with the results of Ofem et al (2013), but they differ from the findings of Olomu et al (2018). The disparity between our findings and those of Olomu et al (2018) could be attributed to differences in the duration of treatment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the significant increase (p<0.05) in PCT could indicate the presence of an infection, while the significant increase (p<0.05) in HCT could suggest dehydration. These findings are consistent with the results of Ofem et al (2013), but they differ from the findings of Olomu et al (2018). The disparity between our findings and those of Olomu et al (2018) could be attributed to differences in the duration of treatment.…”
Section: Discussionsupporting
confidence: 86%
“…These findings are consistent with the results of Ofem et al (2013), but they differ from the findings of Olomu et al (2018). The disparity between our findings and those of Olomu et al (2018) could be attributed to differences in the duration of treatment.…”
Section: Discussionsupporting
confidence: 86%
“…A secondary data analysis of the Uganda Malaria Indicator Survey of 2014 reported an increasing malaria parasite prevalence among children under 5 years associated with severity of anemia [33]. Studies in Ethiopia [34], Nigeria [35], and Mali [36] reported the increased focus of malaria prevention strategies to children under 5 years as being the most affected. In a community level study in Malawi, children under 5 years and those between 5 and 19 years were reported to benefit equally from community bed net coverage [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that children <5 years were less affected than the 5-18 age group because the children are given priority by their guardians to sleep under LLINs, compared with older children. Even at national strategic level, this phenomenon is depicted where children under 5 years are targeted for chemoprevention [35,36] and targeted bed net distribution [25][26][27].…”
Section: Discussionmentioning
confidence: 99%